Answer:
s(t) = -4.9t² + 39.2t
Step-by-step explanation:
Given the projectile motion of an object can be modeled using s(t) = gt2 + v0t + s0, where g is the acceleration due to gravity, t is the time in seconds since launch, s(t) is the height after t seconds, v0 is the initial velocity, and s0 is the initial height. The acceleration due to gravity is –4.9 m/s²
Given
g = -4.9m/s²
v0 = 39.2m/s
s0 = 0m (the initial height)
On substituting into the formula;
s(t) = gt² + v0t + s0
s(t) = -4.9t² + 39.2t + 0
s(t) = -4.9t² + 39.2t
This gives the equation that models the height
<span><span>9<span>(6j+2+j)</span></span><span>9<span>(6j+2+j)</span></span></span>Add <span><span>6j</span><span>6j</span></span> and <span>jj</span> to get <span><span>7j</span><span>7j</span></span>.<span><span>9<span>(7j+2)</span></span><span>9<span>(7j+2)</span></span></span>Apply the distributive property.<span><span>9<span>(7j)</span>+9⋅2</span><span>9<span>(7j)</span>+9⋅2</span></span>Multiply <span>77</span> by <span>99</span> to get <span>6363</span>.<span><span>63j+9⋅2</span><span>63j+9⋅2</span></span>Multiply <span>99</span> by <span>22</span> to get <span>1818</span>.<span>63j+<span>18</span></span>
Answer:
a) v = 12.21m/s
a = 4.07 m/s²
b)v = 11.24m/s
a = 3.75 m/s²
Step-by-step explanation:
a) Dividing the moviment into two parts:
I - With acceleration
v = v₀ + at
s = s₀ + v₀t + at²/2
- v₀ = 0
- s₀ = 0
- a = ?
- v = ?
- t = 3s
- s = x
v = v₀ + at
v = 3a ⇒ a = v/3
s = s₀ + v₀t + at²/2
x = v/3.3²/2
x = 3v/2
II - Uniform
s = s₀ + vt
s = 100
s₀ = x
v = v
t = 9.69 - 3 = 6.69s
s = s₀ + vt
100 = x + v*6.69
100 = x + 6.69v
As x = 3v/2
100 = 3v/2 + 6.69v
100 = 1.5v + 6.69v
100 = 8.19v
v = 12.21m/s
a = v/3 = 4.07 m/s²
b) Dividing the moviment into two parts:
I - With acceleration
v = v₀ + at
s = s₀ + v₀t + at²/2
- v₀ = 0
- s₀ = 0
- a = ?
- v = ?
- t = 3s
- s = x
v = v₀ + at
v = 3a ⇒ a = v/3
s = s₀ + v₀t + at²/2
x = v/3.3²/2
x = 3v/2
II - Uniform
s = s₀ + vt
s = 200
s₀ = x
v = v
t = 19.30 - 3 = 16.30s
s = s₀ + vt
200 = x + v*16.3
100 = x + 16.3v
As x = 3v/2
200 = 3v/2 + 16.3v
200 = 1.5v + 16.3v
200 = 17.8v
v = 11.24m/s
a = v/3 = 3.75 m/s²
Answer:
x=12
Step-by-step explanation:
3.6x=1.6x+24
We simplify the equation to the form, which is simple to understand
3.6x=1.6x+24
We move all terms containing x to the left and all other terms to the right.
+3.6x-1.6x=+24
We simplify left and right side of the equation.
+2x=+24
We divide both sides of the equation by 2 to get x.
x=12
Ok so to start, your unknown numbers will ne represented as x. The equation looks like this: x+x+1+x+2=228. You have your unknown number, the number plus one, and the numner plus two. To find the answer you divide 228 by 3. Those numbers are all equal though,so you play around with them until you get 75+75+1+75+2=228